Evaluation of Bluetongue Virus (BTV) Antibodies for the Immunohistochemical Detection of BTV and Other Orbiviruses - Lean, Fabian Z. X. (Microorganisms, 2020)
The detection of bluetongue virus (BTV) antigens in formalin-fixed tissues has been challenging; therefore, only a limited number of studies on suitable immunohistochemical approaches have been reported. This study details the successful application of antibodies for the immunohistochemical detection of BTV in BSR variant baby hamster kidney cells (BHK-BSR) and infected sheep lungs that were formalin-fixed and paraffin-embedded (FFPE). BTV reactive antibodies raised against non-structural (NS) proteins 1, 2, and 3/3a and viral structural protein 7 (VP7) were first evaluated on FFPE BTV-infected cell pellets for their ability to detect BTV serotype 1 (BTV-1). Antibodies that were successful in immunolabelling BTV-1 infected cell pellets were further tested, using similar methods, to determine their broader immunoreactivity against a diverse range of BTV and other orbiviruses. Antibodies specific for NS1, NS2, and NS3/3a were able to detect all BTV isolates tested, and the VP7 antibody cross-reacted with all BTV isolates, except BTV-15. The NS1 antibodies were BTV serogroup-specific, while the NS2, NS3/3a, and VP7 antibodies demonstrated immunologic cross-reactivity to related orbiviruses. These antibodies also detected viral antigens in BTV-3 infected sheep lung. This study demonstrates the utility of FFPE-infected cell pellets for the development and validation of BTV immunohistochemistry.